Analysis of The Application of Business Ethics in Online Buying and Selling Transactions on The Shopee Marketplace - Irma Rahmayani Marpaung; Zuhrinal M Nawawi; Nuri Aslami (International Journal Labs, 2021)
In online buying and selling transactions, a seller is required to not intentionally contradict his words and actions in his business. The seller must have a mandate by displaying an attitude of openness, honesty, optimal service, and doing good with all things, especially in relation to public service. That there are several problems that occur in online buying and selling transactions, including the existence of sellers who post pictures on Shoppe that do not match the original. This study aims to analyze the application of business ethics in online buying and selling transactions on the shopee marketplace. This type of research is juridical-normativeor normative legal research. The nature of this research is descriptive-analytical research. Primary data is research material in the form of documented rules, norms about business ethics and the concept of buying and selling online. Data collection techniques in this study using literature, documentation and interviews. Techniques Data analysis is done by inductive thinking. The results show that: the application of business ethics in online buying and selling transactions on the shopee marketplace, has not applied good business ethics. Because there are still acts of lying and also posting pictures that do not match the original.